Genomic and Phenotypic Analyses of Acinetobacter baumannii Isolates From Three Tertiary Care Hospitals in Thailand - Loraine, Jessica; Heinz, Eva; Soontarach, Rosesathorn; Blackwell, Grace A.; Stabler, Richard A.; Voravuthikunchai, Supayang P.; Srimanote, Potjanee; Kiratisin, Pattarachai; Thomson, Nicholas R.; Taylor, Peter W. (Frontiers in Microbiology, 2020)
Antibiotic resistant strains of Acinetobacter baumannii are responsible for a large and increasing burden of nosocomial infections in Thailand and other countries of Southeast Asia. New approaches to their control and treatment are urgently needed and an attractive strategy is to remove the bacterial polysaccharide capsule, and thus the protection from the host’s immune system. To examine phylogenetic relationships, distribution of capsule chemotypes, acquired antibiotic resistance determinants, susceptibility to complement and other traits associated with systemic infection, we sequenced 191 isolates from three tertiary referral hospitals in Thailand and used phenotypic assays to characterize key aspects of infectivity. Several distinct lineages were circulating in three hospitals and the majority belonged to global clonal group 2 (GC2). Very high levels of resistance to carbapenems and other front-line antibiotics were found, as were a number of widespread plasmid replicons. A high diversity of capsule genotypes was encountered, with only three of these (KL6, KL10, and KL47) showing more than 10% frequency. Almost 90% of GC2 isolates belonged to the most common capsule genotypes and were fully resistant to the bactericidal action of human serum complement, most likely protected by their polysaccharide capsule, which represents a key determinant of virulence for systemic infection. Our study further highlights the importance to develop therapeutic strategies to remove the polysaccharide capsule from extensively drug-resistant A. baumanii during the course of systemic infection.